Urban regeneration and urban resilience planning through connectivity: the importance of this principle of new urbanism - Cysek-Pawlak, Monika; Krzysztofik, Sylwia; Makowski, Andrzej (European Spatial Research and Policy, 2023)
Urban regeneration, which is increasingly having to include methods of adapting urban areas to escalating climate change, is one of the main challenges for the contemporary development of European cities, especially in densely built-up central areas. This multi-level process requires major financial outlays, which is why it is so important to identify the factors that ensure the effectiveness of implemented projects. This article attempts to define the meaning of the New Urbanism principle of connectivity, ensuring freedom of movement in the urban regeneration process. The conducted research has been intended to verify the hypothesis that improving connectivity is critical for the success of the processes of regenerating and improving resilience in degraded urban fabric. The research was conducted using the area regeneration of the centre of Lodz as an example, being the largest project of this type in Poland. The analyses were made by comparing the current status, based on an inventory of the existing situation, and the planned status on the basis of design documentation. The research demonstrates that increasing connectivity will improve the accessibility of properties located within municipal quarters and will help obtain more attractive public spaces. The planned activities will also help bolster climate change in the location by increasing green areas, improving the use of wasteland, and by developing a network of green infrastructure. The execution of the revitalisation project in the centre of Lodz will not only improve the quality of space, but will also increase the resilience of the intensively urbanised inner-city areas to climate change.